1990
DOI: 10.1113/jphysiol.1990.sp018324
|View full text |Cite
|
Sign up to set email alerts
|

The contractile response during steady lengthening of stimulated frog muscle fibres.

Abstract: SUMMARY1. Steady lengthenings at different velocities (0-025-1.2 ,tm/s per half-sarcomere; temperature 2-5-5°C) were imposed on isolated frog muscle fibres at the isometric tetanus plateau by means of a loudspeaker motor. The lengthening at the sarcomere level was measured by means of a striation follower either in fixed-end or in lengthclamp mode. The force response was measured by a capacitance gauge transducer (resonance frequency 50 kHz). Preparations showing gross non-homogeneity during lengthening were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

38
358
4

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 288 publications
(404 citation statements)
references
References 34 publications
38
358
4
Order By: Relevance
“…The fitted ratio values for stimulated flexors and extensors of 1.5 − 1.7 were higher than the value of 1.4 reported by Dudley et al (1990) and may be due to the inclusion of measured torque at higher eccentric velocities and / or the fitting procedure giving an extrapolated eccentric maximum value. Indeed, the fitted ratio values in this study fall more in line with the measured in vitro tetanic values reported in the literature of 1.6 − 2.0 (Katz, 1939;Délèze, 1961;Edmann, 1988;Harry et al, 1990;Lombardi and Piazzesi, 1990;Krylow and Sandercock, 1997).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The fitted ratio values for stimulated flexors and extensors of 1.5 − 1.7 were higher than the value of 1.4 reported by Dudley et al (1990) and may be due to the inclusion of measured torque at higher eccentric velocities and / or the fitting procedure giving an extrapolated eccentric maximum value. Indeed, the fitted ratio values in this study fall more in line with the measured in vitro tetanic values reported in the literature of 1.6 − 2.0 (Katz, 1939;Délèze, 1961;Edmann, 1988;Harry et al, 1990;Lombardi and Piazzesi, 1990;Krylow and Sandercock, 1997).…”
Section: Discussionsupporting
confidence: 79%
“…The lower end of this range is similar to values reported in previous in vivo stimulation studies for the quadriceps (Dudley et al, 1990;Westing et al, 1991) soleus (Pinniger et al, 2000) and adductor pollicis (De Ruiter et al, 2000;Lee and Herzog, 2002). While the upper end is similar to values found in previous in vivo stimulation studies for the first dorsal interosseus (Cook and McDonagh, 1995) and in vitro studies for mouse and frog muscle fibres (Katz, 1939;Délèze, 1961;Edmann, 1988;Lombardi and Piazzesi, 1990;Krylow and Sandercock, 1997).…”
Section: Discussionsupporting
confidence: 76%
“…Force response of activated muscles or single muscle fibers to ramp stretches has been extensively studied in the past by a number of authors (27)(28)(29)(30), starting from the pioneering experiments of Katz (31). Most of these studies were performed with slow stretching speeds and mainly aimed at investigating the mechanism of the steady force increase occurring during stretching.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the stretch produced during eccentric contractions might shift myosin heads into a strongly bound state (Lombardi and Piazzesi, 1990). This, in turn, would reduce during eccentric contractions the age-related force deficits commonly observed during either isometric or concentric contractions (Phillips et al, 1991).…”
Section: Cellular Mechanismsmentioning
confidence: 99%